The Effect of Self-Concept and Achievement Motivation on Students' Biology Learning Outcomes in Public Senior High Schools - Tri Widya Ramadhani AY; Muhiddin Palennari; Muhammad Arsyad; Firdaus Daud; Halimah Husain (Postgraduate, University of Mataram, 2026)
Quality education plays a crucial role in developing adaptive, innovative, and competitive individuals. In biology learning, students’ achievement is influenced not only by instructional factors but also by psychological aspects, particularly self-concept and achievement motivation. This study aims to examine the effect of self-concept and achievement motivation on the biology learning outcomes of students in public senior high schools in Sidenreng Rappang (Sidrap) Regency.This research used a quantitative ex post facto design. The population consisted of 2,361 students, with a sample of 160 selected through stratified random sampling. Data were collected using questionnaires and documentation, then analyzed through descriptive and inferential statistics, including regression analysis at a 0.05 significance level. The results indicate that self-concept and achievement motivation are generally at a moderate level, while biology learning outcomes are relatively good. Self-concept has a significant effect (R = 0.763; 58.2%), and achievement motivation also shows a significant effect (R = 0.772; 59.6%). Simultaneously, both variables contribute 60.8% (R = 0.780), with achievement motivation being slightly more dominant. These findings highlight the importance of strengthening students’ self-concept and motivation to improve biology learning outcomes through supportive and student-centered learning environments.